The Consistency of the Use of Inflectional and Derivational Affixes for Word Formation in Students’ Writing - Arga Kusuma, Arif; Saleh, Mursid (Universitas Negeri Semarang, 2017)
To master writing skill, students must use grammatical function correctly in writing, especially the use of inflectional and derivational affixes. Unfortunately, in the real situation, they have errors while trying to use inflectional and derivational affixes in word formation in writing process. It means that there is no consistency in using them. Then, it was needed to conduct a study to investigate the case widely to prove the truth and to find out the difficulties. The objects of the study are: 1) to explore the teacher's preparation of teaching writing dealing with the use of inflectional and derivational affixes for word formation; 2) to investigate the process of how the teaching writing runs in occasion of using inflectional and derivational affixes; 3) to analyze the procedures and the result of the students' way of using inflectional affixes for word formation in writing a text; 4) to analyze the procedures and the result of the students' way of using derivational affixes for word formation in writing a text; 5) to analyze the comparison between the students' performance of inflection usage and the use of derivation; 6) to investigate the difficulties faced by students in using inflectional and derivational affixes in writing text. The study was conducted using qualitative case study. The instruments were teacher interviews, documents observation, classroom observations, and student interviews. The subject of the study was the eleventh graders of SMA NU 03 MualliminWeleri. The results showed that there were errors in the students' use of inflectional and derivational affixes in writing texts.